Student’s Aspirations and Powerful Geography: A Practical Approach in Costa Rica’s Higher Education - Cascante Campos, José Alejandro (2024)
The geography undergraduate program at the University of Costa Rica aims to prepare future professionals who can analyze human-environment spatial interactions while addressing current social and environmental issues. To accomplish this, the program offers students access to powerful geographic knowledge by linking their professional aspirations and interests with meaningful geographic learning. The following chapter shows the results of the development of a powerful instructional practice in environmental geography and GIS, where fourth-year students determined suitable sites for developing reforestation purposes in a mountain landscape. The activity employed a “bottom-up” approach, combining the geography student’s professional aspirations survey and the insights about the importance of geography knowledge at work from a geographer working in an area of greater interest reported by students. The information is used to design and apply a controlled geo-inquiry on GIS and environmental modelling. The results of the instructional practice provided valuable insights into how students acquire and apply new powerful geographic knowledge to address environmental issues in real-life working scenarios in Costa Rica.